A countrywide molecular survey leads to a seminal identification of the invasive cattle tick Rhipicephalus (Boophilus) microplus in Cameroon, a decade after it was reported in Côte d’Ivoire - Silatsa, B.A.; Kuiate, J.-R.; Njiokou, F.; Simo, G.; Feussom, J.-M.K.; Tunrayo, A.; Amzati, G.S.; Bett, Bernard K.; Bishop, Richard P.; Githaka, Naftaly W.; Opiyo, S.O.; Djikeng, Appolinaire; et al. (Elsevier, 2019)
The cattle tick Rhipicephalus microplus is the most important arthropod vector of livestock diseases globally. Since its introduction in West Africa a decade ago, it has been reported in Ivory Coast, Benin, Togo, Mali, Burkina Faso and Nigeria with potentially far-reaching adverse impacts on the livestock sector in the region. Cameroon is located on a major route for transboundary cattle trade between Central and West Africa and it is therefore at risk from R. microplus invasion. This study investigated the occurrence of R. microplus in Cameroon, the genetic polymorphism of the tick and population structure of isolates from different regions of the country to provide data that underpin the design of future vector control programs.